KARAKTERISTIK AKTIVITAS PEDAGANG KAKI LIMA DI SEKITAR JALAN POROS KOTA ABEPURA - Inayatul Ilah Nashruddin; Hazrul H. (DINAMIS, 2014)
The presence of street vendors in the city of Abepura experiencing growth and increase thenegative impact fisual the face of the city. In addition, the location of the trade, which generallyuse a portion of the road / pavement and public facilities to make such a designation does notfunction optimally fit. On the other side of the street vendors is one source of livelihood for themajority of citizens and drive the local economy. Therefore, it is important to do the arrangementand management of the existence of street vendors so that the economy can continue tooperate and be fisual kept tidy and does not damage the function of public space. The purposeof this study was to identify the characteristics of street vendors around the shaft of Abepuracity, as a basis for policy formulation and regulation of street vendors in the city of Abepura. Themethod used is descriptive qualitative and quantitative descriptive. The approach taken is todetermine the characteristics of the activities of street vendors, street vendors sitecharacteristics, and consumer perceptions of the existence and activities of street vendors.Quantitative analysis techniques used include frequency distributions and cross-tabulations.The end result of this research is the profile of the street vendors, the characteristics of streetvendors, street vendors of consumer profiles, as well as consumer perceptions of the existenceand activities of street vendors, so that could be the basis for the city government in policyformulation and structuring of street vendors in the city of Abepura city for the creation of acomfortable environment.